Dopamine Transporter Single-Photon Emission Computerized Tomography Supports Diagnosis of Akinetic Crisis of Parkinsonism and of Neuroleptic Malignant Syndrome. Issue 13 (April 2015) - Martino, G.; Capasso, M.; Nasuti, M.; Bonanni, L.; Onofrj, M.; Thomas, A.; Schaller., Bernhard
<x xml:space="preserve">Abstract</x> Abstract Akinetic crisis (AC) is akin to neuroleptic malignant syndrome (NMS) and is the most severe and possibly lethal complication of parkinsonism. Diagnosis is today based only on clinical assessments yet is often marred by concomitant precipitating factors. Our purpose is to evidence that AC and NMS can be reliably evidenced by FP/CIT single-photon emission computerized tomography (SPECT) performed during the crisis. Prospective cohort evaluation in 6 patients. In 5 patients, affected by Parkinson disease or Lewy body dementia, the crisis was categorized as AC. One was diagnosed as having NMS because of exposure to risperidone. In all FP/CIT, SPECT was performed in the acute phase. SPECT was repeated 3 to 6 months after the acute event in 5 patients. Visual assessments and semiquantitative evaluations of binding potentials (BPs) were used. To exclude the interference of emergency treatments, FP/CIT BP was also evaluated in 4 patients currently treated with apomorphine. During AC or NMS, BP values in caudate and putamen were reduced by 95% to 80%, to noise level with a nearly complete loss of striatum dopamine transporter-binding, corresponding to the "burst striatum" pattern. The follow-up re-evaluation in surviving patients showed a recovery of values to the range expected for Parkinsonisms of same disease duration. No binding effects of apomorphine were observed. By showing the outstanding binding reduction, presynaptic dopamine transporter ligand can provide instrumental evidence of AC in Parkinsonism and NMS.